A study on clinical profile of acute stroke - Itagi, Avinash; G., Bharat; Biradarpatil, Pooja; Pattanashetti, Laxmi (International Journal of Advances in Medicine, 2020)
Background: Stroke or cerebrovascular accident is one of the leading causes of morbidity and mortality in adult life. Ischemic strokes are most common type of strokes and they account for 80-85% of cerebrovascular accidents worldwide. Hypertension, diabetes, dyslipidemia and smoking have been identified as major risk factors. Present study was undertaken to evaluate the clinical and investigation profile of different types of strokes. Methods: A total of 100 patients with brain stroke from November 2015 to October 2016 were included. Adult patients with stroke who attended the emergency department within 24 hours of attack were included. Patients with known chronic liver or kidney diseases, transient ischemic attack, active infections, history of neoplasia and alcoholic patients were excluded from the study. A thorough physical examination was conducted and stroke was defined as per World Health Organization criteria. Blood investigations were done including Magnetic resonance imaging and computed tomography scan. The data obtained was coded and entered into Microsoft excel worksheet. The data was analyzed using SPSS statistics software version 20.0. Results: Majority of the patients (71.00%) were males and 29.0% of the patients were females. Most of the patients were aged between 61 to 70 years (27.00%). Most of the patients had ischaemic stroke (80.00%) followed by haemorrhagic stroke (20%). Conclusions: Ischemic stroke is the more common as compared to hemorrhagic stroke. Detection of vascular risk factors and primary prevention measures should be initiated during late adolescence or early adulthood.